2018
DOI: 10.1145/3183339
|View full text |Cite
|
Sign up to set email alerts
|

How Far We Have Progressed in the Journey? An Examination of Cross-Project Defect Prediction

Abstract: Background. Recent years have seen an increasing interest in cross-project defect prediction (CPDP), which aims to apply defect prediction models built on source projects to a target project. Currently, a variety of (complex) CPDP models have been proposed with a promising prediction performance. Problem. Most, if not all, of the existing CPDP models are not compared against those simple module size models that are easy to implement and have shown a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 111 publications
1
101
0
1
Order By: Relevance
“…In the experiments, we use three widely used datasets: ReLink, AEEEM, and MORPH. Table shows the characteristics of these datasets.…”
Section: Experiments Design and Results Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the experiments, we use three widely used datasets: ReLink, AEEEM, and MORPH. Table shows the characteristics of these datasets.…”
Section: Experiments Design and Results Analysismentioning
confidence: 99%
“…Threats to the external validity of our study are that the observed experimental results may not be applicable to other software projects. To guarantee the representative of experimental subjects, we choose the three extensively used datasets AEEEM, MOPRH, and ReLink …”
Section: Experiments Design and Results Analysismentioning
confidence: 99%
See 3 more Smart Citations